The Effects of 8 Weeks of Moderate-Intensity Aerobic Exercise on Serum Irisin and Leptin Levels in Obese Women in Their 20s - Tae-Hyung Lee; Jae-Myun Ko (운동과학)
PURPOSE This study aimed to investigate the effects of 8 weeks of moderate-intensity aerobic exercise on body composition and serum irisin and leptin levels in obese women. METHODS Obese women in their 20s were divided into an aerobic exercise group (AEG; n=8) and a control group (CON; n=8). Aerobic exercise was conducted at an intensity of 65-70% of the maximal oxygen uptake, with a target energy expenditure of approximately 1,000 kcal/week (350 kcal/session) to promote health. To assess the effects of exercise, body weight and body fat percentage were measured before and after the intervention. Blood samples were collected to analyze serum irisin and leptin levels. RESULTS The aerobic exercise group achieved a reduction in body weight and body fat percentage and exhibited increased serum irisin levels. Conversely, serum leptin levels were seen to decrease. CONCLUSIONS This study confirmed that moderate-intensity aerobic exercise is effective in reducing body weight and body fat in obese individuals and positively influences serum irisin and leptin levels. Furthermore, these findings provide a basis for establishing exercise volume during workouts, highlighting the significance of these experimental results.